2012
DOI: 10.1007/s00436-012-3009-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sex and locality on the abundance of lice on the wild rodent Oligoryzomys nigripes

Abstract: Various factors can affect the parasite distribution on a host. In this study, the influence of sex, body size, and locality of a rodent host, Oligoryzomys nigripes, on lice abundance was investigated. A generalized linear model indicated that the sex and locality of O. nigripes significantly contributed to the variation in lice abundance on the host. The male bias of lice parasitizing the rodent host O. nigripes may be associated with intersexual differences in physiology and behavior, while locality differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 45 publications
2
18
2
Order By: Relevance
“…Kiffner et al (2014) observed that flea abundance was positively related to the body mass of host rodents. Fernandes et al (2012) found that the sex and locality of O. nigripes significantly contributed to the variation in lice abundance on each host. Ectoparasites that do not spend their entire life cycle on the host can be less influenced by factors such as the immunological sex differences of the host species, and the co-occurrence of phylogenetically close host species in the environment.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Kiffner et al (2014) observed that flea abundance was positively related to the body mass of host rodents. Fernandes et al (2012) found that the sex and locality of O. nigripes significantly contributed to the variation in lice abundance on each host. Ectoparasites that do not spend their entire life cycle on the host can be less influenced by factors such as the immunological sex differences of the host species, and the co-occurrence of phylogenetically close host species in the environment.…”
Section: Discussionmentioning
confidence: 97%
“…The parasitic exchange can be influenced by the host density and the number of host species sharing the same parasites (Arneberg et al 1998;Krasnov et al 2002;Fernandes et al 2012). Fernandes et al 2012 showed that the abundance of lice parasitizing the host Oligoryzomys nigripes in ESI was significantly higher than in ESMG, probably as a reflection of both a higher host density and a greater number of host species occurring in ESI.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations